The Influence of Tutorial Videos of Making Basic Patterns of Women's Body on The Learning Outcomes of Deaf Students - Siti Maisyarah Hasibuan; Soeprijanto Soeprijanto; Asep Supena (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to see the impact of a learning design using video tutorials to improve the learning outcomes of deaf students. This research was conducted at SLB Negeri Binjai with a total sample of 8 people who participated in a fashion skills program. The research method used is quasi-experimental with a time series design approach. Data analysis was performed using Ms. software. Excel and SPSS. The results showed that video tutorials on making the archetype of a woman's body can provide a positive increase in the learning outcomes of deaf students which can be seen from the results of the pretest and posttest of students who continue to experience an increase in learning outcomes.